Pembekalan Sediaan Obat Pada Anak-Anak SDN 02 Candirejo Sebagai Agen Apoteker Kecil - Hati, Anita Kumala; Oktianti, Dian; Zaskia, Annisa Vera; Poety, Cresensia Apolonia Da Cruz; Azahra, Intan; Chotifah, Tila Noer (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
"Little Pharmacist" is a program to empower children by providing a basic understanding of the duties and roles of pharmacists, the names of medicines, indication, dosage forms, and how to use them correctly. The “Little Pharmacist” program aims to introduce the pharmacist profession and increase general knowledge about medicines from an early age. Providing activities for children must use interesting, child-friendly and innovative methods through learning experiences. The aim of this community service activity is to increase children's knowledge, especially grade 5 students at SDN 02 Candirejo, about the names of medicines, their properties, dosage forms and the correct way to use them. Community service activities carried out using a demonstration approach and discusion sessions will make it easier for elementary school children to learn about medicines in an easy and fun way so that children can absorb knowledge well. This community service activity was attended by 25 grade 5 students of SDN 02 Candirejo, West Ungaran District, Semarang Regency. The implementation uses a demonstration method, where the service team provides knowledge about the name of the drug, dosage form, indications, and the correct way to use it through the experience of seeing the drug product. Evaluation of the success of the activity is measured by observing students when demonstrating their learning experiences about drugs. As a result, each student was able to identify a medicinal product including the name of the drug, dosage form, indications and how to use it properly.